Media Youtube dalam Pembelajaran Daring di Era Pandemi - Lilis Setiyo Rini; Gunawan Sridiyatmiko (Proceedings Series on Social Sciences & Humanities, 2022)
The purpose of this study was to find out youtube media in brave learning in the pandemic era, to describe the effect of using youtube media in brave learning in the covid 19 era, and to find out the role of teachers in implementing the use of youtube media in the brave learning process. This research was conducted in an elementary school environment, qualitative research methods. The primary data in this study is a bold learning activity using youtube media which will be divided into several screenshots of youtube video images in conducting the analysis. While secondary data obtained by researchers based on literature studies to complement the data held by researchers, including books and scientific articles. The results of the research are: 1) YouTube learning media is very meaningful in bold learning so that it can increase students' interest and motivation to learn, 2) In using YouTube media, teachers are creative and innovative in making interesting learning videos, 3) Utilization of YouTube media in learning daring can make it easier for students to learn, anywhere and anytime, because youtube media can be accessed by students easily.